Influence of the applied layer on the state of stress in a bimetallic perforated plate under two load variants (Fracture and Structural Integrity, 2021)
The paper presents the results of the analysis of the influence of the applied plate layer on the state of stress in the bimetallic perforated plate. The finite element method ANSYS program was used for numerical calculations. The paper presents the results of stress tests for a single-layer clad plate made of S355J2 steel and a bimetallic perforated plate consisting of layers made of S355J2 steel and titanium. In addition, the study presents the results of the research on the influence of the method of loading, i.e. the concentrated force P in the geometric center of the plate and the external pressure q on the entire surface of the plate, and the method of support, i.e. free support and fixed, on the location of stress concentration zones in the bimetallic circular perforated plate. It has been shown that the presence of a perforated layer in the plate reduces the value of the equivalent von Mises stress by a minimum of approximately 30% in the base (steel) layer.
Keywords: Applied layer; Base layer; Stress analysis; Numerical calculations; FEM